Arginase 1: An Unexpected Mediator of Pulmonary Capillary Barrier Dysfunction in Models of Acute Lung Injury - Lucas, Rudolf; Czikora, Istvan; Sridhar, Supriya; Zemskov, Evgeny A.; Oseghale, Aluya; Circo, Sebastian; Cederbaum, Stephen D.; Chakraborty, Trinad; Fulton, David; Caldwell, Robert W.; Romero, Maritza J. (Frontiers in Immunology, 2013)
The integrity of epithelial and endothelial barriers in the lower airspaces of the lungs has to be tightly regulated, in order to prevent leakage and to assure efficient gas exchange between the alveoli and capillaries. Both G- and G+ bacterial toxins, such as LPS and pneumolysin, respectively, can be released in high concentrations within the pulmonary compartments upon antibiotic treatment of patients suffering from acute respiratory distress syndrome (ARDS) or severe pneumonia. These toxins are able to impair endothelial barrier function, either directly, or indirectly, by induction of pro-inflammatory mediators and neutrophil sequestration. Toxin-induced endothelial hyperpermeability can involve myosin light chain phosphorylation and/or microtubule rearrangement. Endothelial nitric oxide synthase (eNOS) was proposed to be a guardian of basal barrier function, since eNOS knock-out mice display an impaired expression of inter-endothelial junction proteins and as such an increased vascular permeability, as compared to wild type mice. The enzyme arginase, the activity of which can be regulated by the redox status of the cell, exists in two isoforms - arginase 1 (cytosolic) and arginase 2 (mitochondrial) - both of which can be expressed in lung microvascular endothelial cells. Upon activation, arginase competes with eNOS for the substrate L-arginine, as such impairing eNOS-dependent NO generation and promoting ROS generation by the enzyme. This mini-review will discuss recent findings regarding the interaction between bacterial toxins and arginase during acute lung injury and will as such address the role of arginase in bacterial toxin-induced pulmonary endothelial barrier dysfunction.